Energy-storage performance of NaNbO3 based multilayered capacitors. Issue 25 (14th June 2021) - Zhu, Li-Feng; Yan, Yongke; Leng, Haoyang; Li, Xiaotian; Cheng, Li-Qian; Priya, Shashank
Abstract : Energy-storage performances of NaNbO3 system were effectively enhanced by composition engineering inducing relaxor behavior and grain refinement. Excellent W rec = 3.7 J cm −3 and η = 82.1% were achieved in the NN-0.04CZ-0.16BNT multilayer capacitors. Abstract : Environmentally friendly NaNbO3 capacitors have a great potential for applications in pulsed-discharge and power conditioning electronic systems because of their AFE-like hysteresis behavior, high saturation polarization and low mass. Here, we demonstrate (0.96 − x )NaNbO3 –0.04CaZrO3 – x Bi0.5 Na0.5 TiO3 (abbreviated as NN-CZ- x BNT) capacitors with high energy storage density ( W rec ) and efficiency ( η ). The performances of capacitors were tuned by the composition induced relaxor behavior and grain refinement which resulted in reduction of hysteresis and increase in the breakdown strength (BDS). Two-step sintering is found to be effective for reducing the grain size of MLCCs to 3 μm, which is 86% smaller as compared to grain size obtained by conventional solid-state sintering (22 μm). Small grain size significantly reduces the leakage current and losses and increases the BDS, yielding excellent W rec = 3.7 J cm −3 and η = 82.1% in the NN-0.04CZ-0.16BNT multilayered capacitors. Results provide a systematic strategy for enhancing the energy storage density and efficiency of dielectric capacitors through the combination of dielectric relaxation and grain size refinement.